1993
DOI: 10.1007/bf02047381
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cultures of the mucosalassociated bacteria in the mechanically prepared colon and rectum

Abstract: Little is known about the mucosal microflora of the colon and rectum at the time of elective surgery. Our objective was to determine the concentrations of anaerobic and aerobic bacteria associated with the mucosa of the mechanically prepared large bowel. Ten patients were studied after a standard polyethylene glycol-electrolyte lavage preparation. No patient had taken antibiotics in the preceding four weeks. Sterile wire brushes passed through the colonoscope during advancement were used to culture the rectal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The epithelial metabolism in the distal colon mainly involves butyrate, and in the proximal epithelium, acetate. Bacterial populations are qualitatively and quantitatively different in the lumen of proximal and distal colons [65], but studies showed that in a given patient similar populations of mucosa-associated bacteria are accommodated along the different parts of the colon irrespective of differences in the luminal content [66][68]. Most CM-producing strains harbor colibactin-encoding pks island or the combination of cnf genes with pks island (79% of CM-producing E. coli ), suggesting an important role of pks island in the distribution of CM-producing E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial metabolism in the distal colon mainly involves butyrate, and in the proximal epithelium, acetate. Bacterial populations are qualitatively and quantitatively different in the lumen of proximal and distal colons [65], but studies showed that in a given patient similar populations of mucosa-associated bacteria are accommodated along the different parts of the colon irrespective of differences in the luminal content [66][68]. Most CM-producing strains harbor colibactin-encoding pks island or the combination of cnf genes with pks island (79% of CM-producing E. coli ), suggesting an important role of pks island in the distribution of CM-producing E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous data have shown that subjects who were exposed to increased levels of nitrosamines, predicted based on higher intake of red meat and processed met, were at a markedly greater increased risk for rectal cancer but not for colon cancer [75]. It can be speculated that the differences between colon and rectum responses may be due to different parameters correlated to the carcinogenesis process such as rate of xenobiotic metabolism, enzyme expression, pro-carcinogenic DNA-adducts formation, bacterial content, morphology and fecal transit time [76,77]. There is a common agreement that microbiota resident within the lumen of the gastrointestinal tract and its metabolism may influence cancer predisposition and etiology [78].…”
Section: Discussionmentioning
confidence: 99%
“…Since bacterial content, rates of xenobiotic metabolism, transit time, morphology, enzymatic expression, and the level of pro-carcinogenic DNA-adducts differ between the proximal colon, distal colon, and rectum (33, 38-39), the degree of susceptibility to the effects of potential carcinogens may vary between sites (33). It is possible that the proximal colon may be more susceptible to the harmful effects of nitrites whereas the distal colon and rectum may be more susceptible to the negative effects of HCAs and PAHs.…”
Section: Discussionmentioning
confidence: 99%